2014
DOI: 10.1177/0194599814528301
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Otitis Externa: Evolving Pathogens and Implications for Diagnosis and Treatment

Abstract: A high index of suspicion for nonpseudomonal organisms should be maintained in patients with signs and symptoms of MOE, especially in those without diabetes. MRSA is an increasingly implicated organism in MOE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…and Aspergillus niger, respectively (12,13). Several therapeutic regimens are employed to treat otitis externa (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…and Aspergillus niger, respectively (12,13). Several therapeutic regimens are employed to treat otitis externa (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Our search of the literature yielded only one other U.S. study examining the epidemiology of MRSA otitis: a 2014 study from Pittsburg Medical Center, which reported an MRSA rate of 15% among malignant otitis externa cases caused by S. aureus . 4 These findings may indicate that MRSA AOE, when not identified and treated early, may more frequently result in advanced disease and complications.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 S. aureus is thought to be the second most common pathogen in acute bacterial otitis externa, with case series identifying S. aureus in up to 40% of cases. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 Studies from Pakistan, Korea and New Zealand found rates of S. aureus AOE above 30%, 10 , 11 , 12 while the most recent study in the U.S. reported rates of 7.8%. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Like in the index case, it is seen commonly in elderly male diabetics in their VI and VII decade of life ( Blyth et al., 2011 ; Das et al., 2019 ; Lee et al, 2008, 2017). Pseudomonas aeruginosa is the commonly isolated organism, representing more than 50% in most of the series, followed by methicillin-resistant Staphylococcus aureus and Klebsiella pneumonia ( Chen et al., 2010 ; Ali et al., 2010 ; Loh and Loh, 2013 ; Stern Shavit et al., 2016 ; Lee et al, 2008, 2017; Hobson et al., 2014 ; Le Clerc et al., 2014 ). Though the causative organism was identified to be Pseudomonas in our case, the culture reports may not always yield positive results ( Ali et al., 2010 ; Loh and Loh, 2013 ; Lee et al, 2008, 2017; Spielmann et al., 2013 ; Le Clerc et al., 2014 ; Sokołowski et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%